Easter Muslim point of view - Deedat, Ahmed (Dubai : Islamic Propagation Center International [production company] ; Kuala Lumpur : SABA Islamic Media [distributor], 1996)
A lectures by Ahmed Deedat, give an Islamic point of view on Easter. This passionate talk was given in front of a capacity crowd at the Sydney Town Hall on the 5th April 1996(Friday Night) as part of Sheikh Ahmed Deedat's Australian tour
Title from container
Speaker: Ahmed Deedat
VCD format
Keywords: Jesus Christ -- Islamic interpretations; Easter